System architecture and key technologies of intelligent, safe and efficient mining for rockburst coal seams - Zhigang DENG; Yunpeng LI; Shankun ZHAO; Yin WANG; Shaogang LI; Linghai KONG; Junjun JIANG; Zhenguo SU; Yizhe LI; Kai QIN (Meikuang Anquan)
At present, the prevention and control of rock burst in coal mines relies on the monitoring and manual analysis of stress, energy, displacement and other data, and implements targeted prevention measures accordingly. After nearly 100 years of unremitting research and practice, remarkable progress has been made in this field in terms of theoretical depth, technological innovation and equipment upgrading. However, in the field of source control and intelligent prevention and control, there are still many challenges and problems. In the selection of the top ten industrial and technological issues by the China Association for Science and Technology in 2023, the expert group unanimously selected “how to achieve intelligent, safe, and efficient mining of coal seams under rock pressure” as a key topic. It points out the direction for the future development of mine burst disaster prevention and control. The intelligent mining of rock burst coal seam is not only a technical problem, but also a complex system engineering problem. Based on more than 40 years of theoretical accumulation and engineering practice, the framework and key technologies of intelligent, safe and efficient coal seam mining system are proposed. First of all, digital twin technology is used to build a fine digital model, deeply detect and analyze the geological structure of the area where the mine is located, accurately measure the characteristics of the regional geostress field and the physical and mechanical properties of coal and rock, and rely on advanced algorithms to carry out engineering distribution of formation change information to achieve “transparency” of geological information. Secondly, in the digital model, the excavation process of shaft, roadway and working face is simulated according to the mine mining design scheme. At the same time, the real-time data of various monitoring systems in the well and underground are combined with the dynamic update and calculation of the mine digital model, which can not only review and analyze the historical engineering effects, but also predict and deduce the impact of future engineering activities. Thirdly, with the help of deep learning and AI technology, the computer can independently learn the holographic data of the mine, make independent decisions on mining and prevention engineering measures according to the real-time changes of monitoring data and engineering activities, and build a standardized communication technology system to realize the interconnection of various equipment in the mine and create an intelligent mine ecosystem. Finally, the intelligent mining equipment control module is developed. Under the guidance of computer intelligent decision, the intelligent control of all kinds of equipment in the whole mine is realized. By independently adjusting the timing of coal mining and pressure relief, optimizing the running speed of coal mining, transportation, lifting and other equipment, fully realizing the intelligent mining of rock burst coal seams, all these provide strong guarantee for the safe production and efficient operation of coal mines.